AN INVESTIGATION INTO IDIOMS AND PROVERBS RELATING TO CHILDREN IN ENGLISH AND VIETNAMESE - Assoc. Prof. Dr. PHAN VĂN HÒA (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Basically study syntactic, semantic and cultural characteristics of English I&P relating to children in comparison with Vietnamese ones in order to provide language learners with a basic knowledge of this field and help them master the meaning of I&P, then translate them to each of these languages.